Interhemispheric Functional Connectivity in Childhood Absence Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
Using a blood oxygen level-dependent resting functional connectivity approach to analyze EEG-fMRI data, the properties of bihemispheric brain networks in 16 patients with childhood absence epilepsy (CAE) were investigated during the interictal period, in a study at Yale University School of Medicine, New Haven, CT.